3D-Printed vs. Heat-Polymerizing and Autopolymerizing Denture Base Acrylic Resins - Perea-Lowery Leila; Gibreel Mona; Vallittu Pekka K; Lassila Lippo V (MDPI, 2022)
The aim of this work was to investigate the effect of two post-curing methods on the mechanical properties of a 3D-printed denture base material. Additionally, to compare the mechanical properties of that 3D-printed material with those of conventional autopolymerizing and a heat-cured denture base material. A resin for 3D-printing denture base (Imprimo®), a heat-polymerizing acrylic resin (Paladon® 65), and an autopolymerizing acrylic resin (Palapress®) were investigated. Flexural strength, elastic modulus, fracture toughness, work of fracture, water sorption, and water solubility were evaluated. The 3D-printed test specimens were post-cured using two different units (Imprimo Cure® and Form Cure®). The tests were carried out after both dry and 30 days water storage. Data were collected and statistically analyzed. Resin type had a significant effect on the flexural strength, elastic modulus, fracture toughness, and work of fracture (p < 0.001). The flexural strength and elastic modulus for the heat-cured polymer were significantly the highest among all investigated groups regardless of the storage condition (p < 0.001). The fracture toughness and work of fracture of the 3D-printed material were significantly the lowest (p < 0.001). The heat-cured polymer had the lowest significant water solubility (p < 0.001). The post-curing method had an impact on the flexural strength of the investigated 3D-printed denture base material. The flexural strength, elastic modulus, fracture toughness, work of fracture of the 3D-printed material were inferior to those of the heat-cured one. Increased post-curing temperature may enhance the flexural properties of resin monomers used for 3D-printing dental appliances.